Interaksi Belajar dalam Pembelajaran Musik Rebana: Kajian Interaksi Simbolik (Universitas Negeri Semarang, 2022)
Social interaction can be understood as a relationship between individuals and individuals or groupswhere there is an action and reaction as a result of the relationship. Symbolic interaction becomes partof social interaction because humans produce meaningful symbols when interacting. This study aimedto analyze the process of social interaction and symbolic meaning in learning rebana music. This studyused qualitative methods with educational and sociological approaches. Data collection techniquesused observation, interviews, and documentation. In addition, the data validity technique used sourcetriangulation. The data analysis technique consisted of three stages: data reduction, data presentation,and conclusions. The results showed that social interaction in rebana learning occurred betweenmembers, trainers and the community. The symbolic interactions produce the meaning of variousobjects in rebana learning. The symbolic meanings attached to the learning interactions of the Al-Maddah Rebana group include the first meaning, namely the rebana symbol for performers and thecommunity, as the context of hablun minallah wa hablun minannaass (relationship with God andhumans). The second meaning is the use of incense and frankincense during the activities of the Al-Maddah Rebana group as a symbol of the practice of the Sunnah of the Prophet Muhammad SAW,namely the Prophet's preference for fragrances. The meaning of the three nonverbal symbols in rebanalearning interactions is the delivery of emotional states. The fourth meaning of reading the Book ofMawlid Ad-Diba' on the shalawat song as a symbol of love for the Prophet Muhammad SAW.